2020
DOI: 10.1097/sla.0000000000003824
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Going Small

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Good venous outflow is as important as vascular inflow and graft size and contributed to the success of LDLT. (20) In conclusion, for patients with MELD > 25 and HRS, the ITT-LDLT approach reduced waitlist mortality by providing earlier access to transplant, particularly within the first month after listing when the mortality risk without transplant was the highest. A consistent survival benefit was observed across all MELD strata.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Good venous outflow is as important as vascular inflow and graft size and contributed to the success of LDLT. (20) In conclusion, for patients with MELD > 25 and HRS, the ITT-LDLT approach reduced waitlist mortality by providing earlier access to transplant, particularly within the first month after listing when the mortality risk without transplant was the highest. A consistent survival benefit was observed across all MELD strata.…”
Section: Discussionmentioning
confidence: 90%
“…Although the success of LDLT is multifactorial, the application of LDLT should not be limited by a certain MELD cutoff. (20) With the advancement of surgical, anesthetic, and perioperative care, many centers that predominately perform DDLT also reported excellent outcomes after LDLT. (5,10,27) Lastly, it is worth noting that right-lobe grafts with inclusion of MHV were the predominant graft type in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hong Kong group 28 reported that GRWR in LDLT could be lowered to 0.6%, even as low as 0.46%, with satisfactory outcomes. However, it needs to be recognized that they used a dividing a factor of 1.19 for converting the value of calculated graft volume (GV) to the expected one.…”
Section: Small -For-size Graftmentioning
confidence: 99%